CHARACTER BUILDING OF STUDENTS WITH COUNSELING SERVICES APPROACH - Atieka, Nurul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2014)
Abstract: Expectations of society, which until now has not significantly met by the world of education in Indonesia, it becomes a challenge to improve the quality of education. The rise of the brawl, the case of drugs and free sex among students makes people pessimistic about the quality of education and educational output. Associated with the various problems that come across, character building of young generation ago into something that absolutely must be done. An understanding of identity, duties, and responsibilities of students, and also habituation to the values and norms in the community becomes a necessity that must be installed. Counseling services as a form of education play a major role in providing assistance to students in order to achieve optimal development. Achieving optimal developmental tasks, and effectively became the foundation of character formation of students and the fulfillment of the expectations of society toward education.Keyword: Character, Counseling Services, Education